EFFICIENCY OF GOVERNMENT SPENDING IN EDUCATION SECTOR IN EAST JAVA 2015-2021 - Friska Mauludhiana; Muhammad Wahed (Jurnal REP (Riset Ekonomi Pembangunan), 2022)
This study aims to determine the level of efficiency of government spending in the education sector in the period of 2015-2021, by using a quantitative approach, Data Envelopment Analysis (DEA). Linear program of non-parametric approach with the model used namely Constant Return to Scale (CRS), which aims to calculate and evaluate efficiency values. The results of this study showed that the level of efficiency for the field of education in five districts/cities varied during the research period. The highest level of efficiency is in Malang Regency, while the lowest efficiency value is in the city of Surabaya. The cause of inefficiency in a regency/city is due to waste in the use of resources and weak management systems.